The Meaning of Communication in Jürgen Habermas' Theory - Sidrys, Inga (Sociologija. Mintis ir veiksmas, 2015)
The article is aimed at a discussion of Habermas' theory of communicative action on two levels: the level of principles of Habermasian ethics and the question of relevance of Habermas' ideas for democratic order. The author develops her argument by reconstructing Habermas notion of communicative rationality and the normative idea of the ideal speech situation. The author discusses the thesis of colonization of the lifeworld by the system and overviews the critiques of the abstract and idealistic form that Habermas illuminates the possibilities of a dialogue between competent agents. In the face of the critiques, the author attempts to discuss the relevance of Habermas' ideas for understanding the practical issues in contemporary societies by overviewing the possible ways that Habermas' ideas were applied.
Keywords: civic society; communicative action; communicative competence; rationalization; ideal speech situation; lifeworld and system; colonization